Phylogeny and taxonomic status evaluation of Dark-sided Narrow-mouthed Frog, Microhyla heymonsi, (Anura: Microhylidae) from Sumatra, Indonesia (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Eprilurahman R, Atmaja VY, Munir M, Ubaidillah R, Arisuryanti T, Smith EN, Hamidy A. 2023. Phylogeny and taxonomic status evaluation of Dark-sided Narrow-mouthed Frog, Microhyla heymonsi, (Anura: Microhylidae) from Sumatra, Indonesia. Biodiversitas 24: 1092-1103. Microhyla heymonsi (Dark-sided narrow-mouthed frog) was once known to be widespread along the continent of Asia from Taiwan to the mainland of east and southeast to Nicobar Islands and Sumatra. Recent studies identified that this species is cryptic species consisting of M. heymonsi itself and several newly described species, i.e., M. daklakensis, M. heymonsi, M. nakkavaram, M. ninhthuanensis, and the possibility of unnamed lineage. In Sumatra, M. heymonsi is not only distributed from the north to south of the mainland but also in the adjacent islands in Nias. Regarding the taxonomic status of Sumatran population, here we used molecular and morphological data to evaluate the taxonomic status of the Sumatran M. heymonsi. The phylogenetic analyses show that the Sumatran M. heymonsi is closest to M. nakkavaram and strongly supported as a member of subgroup M. heymonsi along with other recognized species, i.e., M. daklakensis, M. heymonsi, M. nakkavaram, and M. ninhthuanensis. The morphological assessment of Sumatran M. heymonsi shows that they are suitable with the morphological characteristic of M. nakkavaram. Both molecular and morphological data strongly support that Sumatran M. heymonsi is identical to the M. nakkavaram from Nicobar Islands. Our results expanded the distribution of M. nakkavaram, not only in Nicobar Islands but also in Sumatra and its adjacent islands. In addition, the phylogenetic tree showed the supported clade of Nicobar and Sumatran M. nakkavaram as sister taxa of the possibly undescribed species from Singapore and Peninsular Malaysia. Further study of this undescribed species is urgent.